Torsion of the testis with perineal ectopy - Boyan Stoykov; Nikolay Kolev; Vladislav Dunev; Pencho Genov (Urology Case Reports, 2020)
Congenital testicular anomalies affect about 5% of newborn boys. Testicular torsion is a rare anomaly that occurs in 1 in 4000 men under the age of 25. Perineal ectopia is an even more rare anomaly. It occurs in less than 1% of all cases of cryptorchidism. In this study, we present a rare case of testicular torsion with perineal ectopia in a boy of 18 months. To establish the anomaly, we used Doppler ultrasound and MRI. We performed inguinal exploration with subsequent detorsion testis and orchiopexy using the dartos pouch technique. Keywords: Perineal ectopic testis, Congenital anomaly, Orchiopexy